On a q-analogue of chang and shan’s identity - He, Bing (Utilitas Mathematica, 2018)
We give a general g-identity which includes as special cases many new and nontrivial identities on binomial coefficients or g-binomial coefficients. In particular, Chang and Shan's identity [SIAM Review, 1983, 25(1): 97] and its analogue are also special cases of this identity. © 2018 Utilitas Mathematica Publishing Inc. All rights reserved.